If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(m + -2n) + 6(n + -2m) = 0 (m * 3 + -2n * 3) + 6(n + -2m) = 0 (3m + -6n) + 6(n + -2m) = 0 Reorder the terms: 3m + -6n + 6(-2m + n) = 0 3m + -6n + (-2m * 6 + n * 6) = 0 3m + -6n + (-12m + 6n) = 0 Reorder the terms: 3m + -12m + -6n + 6n = 0 Combine like terms: 3m + -12m = -9m -9m + -6n + 6n = 0 Combine like terms: -6n + 6n = 0 -9m + 0 = 0 -9m = 0 Solving -9m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-9'. m = 0 Simplifying m = 0
| 8+e=.2e+.8(e-10) | | 3r^3+15r^2=72r | | -2.8(x+4.9)=18.2 | | 2-a+3=-2 | | y+12/5=79/15 | | 2x+1=-12 | | (-3)/(-6) | | 2x+1=-23+5x | | 62/3+(51/4-37/8) | | 6+x=6x-44 | | 2x-6=3x-1 | | (5x+8)(x-8)=0 | | 1/2+v=14/25 | | 4q+6(p-2q)= | | 56/9-r=39/4 | | 4x+9=2x+27 | | n^2+6n-14=2 | | (x+8)(x-5)(-x+7)=0 | | 32b+8= | | (x^2/63)+(16x/63)+1=0 | | x^2-8x=x(-3+x) | | 4(5+2t)=9(2+t) | | 39.75+9.50*h=115.75 | | X/5+9=4-1 | | 4x+6=-1+5x | | u+3/7=6 | | X^5+9=4-1 | | x(12x+20)=25 | | -(1.2x+7)+1.5x= | | 6.5-y=5.06 | | 7/9w=56 | | 2x+3=3x-9 |